The impact of a disaster medicine clinical training program on medical students’ disaster literacy - Aysel Başer; Zeynep Sofuoğlu (PeerJ)
Background This study was conducted to assess how students’ disaster literacy was affected by the Disaster Medicine Clinical Training Program at the Izmir Democracy University Faculty of Medicine (IDUFM) during the academic year 2022–2023. Methods Using an experimental method involving experimental and control groups, measurements were made at different times. The sample consisted of 5th-year students at IDUFM for the experimental group, while the control group was composed of 3rd- and 4th-year students from different buildings with limited interaction with the experimental group. The clinical training program was organized to improve the clinical practice skills of students in the field of disaster medicine and provide theoretical information. Throughout their internship, the students were provided with a program including information on types of disasters, preparation, response, relief, emergency surgical procedures, hospital disaster plans, national and international organizations and institutions working in disasters, and other relevant topics. The Disaster Literacy Scale (DLS) was used to collect data. This scale is a self-report scale that was developed to evaluate knowledge levels about disasters. In this study, the scale was applied as a pretest and a posttest, and the obtained data were analyzed using independent samples and paired-sample t-tests. Result The DLS scores of the experimental group showed significant improvement after the training program compared to their pretest scores (Total Scale: p < 0.001, Damage Mitigation: p = 0.002, Preparation: p < 0.001, Response: p < 0.001, and Relief: p = 0.004). When comparing the posttest results of the experimental group with the control group, the experimental group demonstrated significantly higher scores in Total Scale (p = 0.01), Damage Mitigation (p = 0.02), Response (p = 0.03), and Relief (p < 0.001). However, no significant differences were observed between the experimental group’s pretest (T1) scores and the control group’s posttest (T3) scores (p > 0.05p > 0.05p > 0.05), indicating that the knowledge levels of the experimental and control groups were homogeneous prior to the training intervention. These findings confirm the effectiveness of the Disaster Medicine Training Program in improving disaster literacy and response skills among medical students. Conclusion This study, which aimed to determine the effects of the Disaster Medicine Clinical Training Program on the disaster literacy of medical students, revealed that the program increased the literacy levels of the students and contributed to their responsible decision-making. It is thought that such education programs can make significant contributions to the effective management of healthcare services in disaster situations.